Coffee consumption and mortality in Japan with 18 years of follow-up: the Jichi Medical School Cohort Study. (February 2021) - Sakamaki, T.; Kayaba, K.; Kotani, K.; Namekawa, M.; Hamaguchi, T.; Nakaya, N.; Ishikawa, S.
Abstract: Objective: Coffee consumption can be expected to reduce mortality due to cardiovascular diseases and cancer. This study tested the hypothesis of an inverse association between coffee intake and all-cause mortality and mortality due to cancer, coronary heart disease, or stroke. Study design: Prospective cohort study. Methods: We analyzed data from the Jichi Medical School Cohort Study, Japan, enrolling 9946 subjects (men/women: 3870/6, 076, age: 19–93 years) from 12 communities. A food frequency questionnaire assessing the subjects' daily coffee consumption was used. Results: During an average follow-up of 18.4 years, the total number of deaths was 2024, including 677 for cancer, 238 for coronary heart disease, and 244 for stroke. Cox proportional hazards models were used to calculate hazard ratios (HRs) and 95% confidence intervals (CIs) of all-cause mortality and cause-specific mortality due to cancer, coronary heart disease, and stroke. Overall, no significant association was shown between coffee consumption and all-cause mortality. In the cause-specific mortality analyses, stroke mortality was significantly lower in those who consumed 1–2 cups of coffee daily (HR [95% CI]: 0.63 [0.42–0.95]) than in those who do not consume coffee, and this association occurred only in men. Conclusion: This study showed no significant association between coffee consumption and all-cause mortality. A U-shaped association between coffee consumption and stroke mortality with a 37% lower stroke mortality, only significant in men who consume 1–2 cups of coffee daily was observed. It is necessary to examine the possibility of intervention studies to reduce stroke mortality through coffee consumption Highlights: This study analyzed the association between coffee consumption and all-cause and cause-specific mortality using a data from the Jichi Medical School Cohort Study. We enrolled 12, 490 subjects from 12 communities in Japan. Food frequency questionnaire assessing the daily coffee consumption was used. No significant association between coffee consumption and all-cause mortality. A U-shaped association between coffee consumption and stroke mortality.